2013
DOI: 10.1186/1472-6963-13-234
|View full text |Cite
|
Sign up to set email alerts
|

A study of physician collaborations through social network and exponential random graph

Abstract: BackgroundPhysician collaboration, which evolves among physicians during the course of providing healthcare services to hospitalised patients, has been seen crucial to effective patient outcomes in healthcare organisations and hospitals. This study aims to explore physician collaborations using measures of social network analysis (SNA) and exponential random graph (ERG) model.MethodsBased on the underlying assumption that collaborations evolve among physicians when they visit a common hospitalised patient, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
0
37
1
Order By: Relevance
“…This group plays a liaison role between the Montreal homeless organisations [1]. A high density can have positive, but also negative aspects [43, 52]. It might indicate the existence of shared values and beliefs among members of the Montreal homeless organisation network, which facilitate information sharing and decision-making [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This group plays a liaison role between the Montreal homeless organisations [1]. A high density can have positive, but also negative aspects [43, 52]. It might indicate the existence of shared values and beliefs among members of the Montreal homeless organisation network, which facilitate information sharing and decision-making [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that focused on the link between collaboration and user outcomes have arrived at conflicting results. Some studies revealed that collaboration between organisations or professionals would increase patient satisfaction [52] and reduce death rates [53], length of hospital stays and hospitalisation costs [54, 55]. Other studies have indicated, however, that other factors such as stability or level of funding can affect the positive association between integration and outcome [7, 56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centralization of a network of collaboration of physicians around a dominant actor has been found instead to be negatively related to performance, in terms of both higher hospitalization cost and higher rate of patients' readmission to hospital (Uddin et al, 2013).…”
Section: Performancementioning
confidence: 99%
“…There are increasing numbers of studies combining different types of social networks and health [57], with scope for possible network interventions [8]. In health care settings [911], these have been used to analyze hierarchies and positions in the network [12, 13], their relationship with hospitalization costs and readmission rates [14], information seeking [15, 16], the adoption of best practices [17], and homophily in advice and friendship networks, the tendency of individuals to associate and bond with similar others [18, 19]. Social networks may play a role in the adoption of health behaviors and practices [20], and homophily, in particular, has been shown to have an effect [21, 22].…”
Section: Introductionmentioning
confidence: 99%